Heme-deficient metabolism and impaired cellular differentiation as an evolutionary trade-off for human infectivity in Trypanosoma brucei gambiense - Horáková, Eva; Lecordier, Laurence; Cunha, Paula; Sobotka, Roman; Changmai, Piya; Langedijk, Catharina J M; Abbeele, Jan Van Den; Vanhollebeke, Benoit; Lukeš, Julius (Nature communications, 2022)
Resistance to African trypanosomes in humans relies in part on the high affinity targeting of a trypanosome lytic factor 1 (TLF1) to a trypanosome haptoglobin-hemoglobin receptor (HpHbR). While TLF1 avoidance by the inactivation of HpHbR contributes to Trypanosoma brucei gambiense human infectivity, the evolutionary trade-off of this adaptation is unknown, as the physiological function of the receptor remains to be elucidated. Here we show that uptake of hemoglobin via HpHbR constitutes the sole heme import pathway in the trypanosome bloodstream stage. T. b. gambiense strains carrying the inactivating mutation in HpHbR, as well as genetically engineered T. b. brucei HpHbR knock-out lines show only trace levels of intracellular heme and lack hemoprotein-based enzymatic activities, thereby providing an uncommon example of aerobic parasitic proliferation in the absence of heme. We further show that HpHbR facilitates the developmental progression from proliferating long slender forms to cell cycle-arrested stumpy forms in T. b. brucei. Accordingly, T. b. gambiense was found to be poorly competent for slender-to-stumpy differentiation unless a functional HpHbR receptor derived from T. b. brucei was genetically restored. Altogether, we identify heme-deficient metabolism and disrupted cellular differentiation as two distinct HpHbR-dependent evolutionary trade-offs for T. b. gambiense human infectivity.
Keywords: hem; Trypanosoma brucei gambiense; Heme; biologická evoluce; buněčná diferenciace; Cell Differentiation; Humans; Biological Evolution; Lipoproteins, HDL; lidé; lipoproteiny HDL